The Britannica Guide to the Ideas that Made the Modern World - Encyclopedia Britannica (Running Press, 2008)
"In the early years of the twenty-first century, ideas first proposed over two hundred years ago could not be more compelling. The Enlightenment of the seventeenth century in response to upheaval and uncertainty laid the foundation stone for modern society. A vital primer on the philosophers, thinkers, and scientists-including Isaac Newton, John Locke, Voltaire and Spinoza-whose thoughts and ideas created the modern world."--Publisher description.